Peran Perguruan Tinggi Mewujudkan Dinamika Kedamaian dalam Kehidupan Masyarakat - Sumardjo, .; Wirakartakusumah, Aman (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2009)
In any civilization, peacefulness or non-violence culture could be the ultimate end of human life. It contains human right principles to be achieved by community, civics, and nation. Albeit, in reality, the situation achieved is diametrically in the opposite to what expected where competition, contravention and social conflict arises very sharply unless a constructive conflict management is applied. The potentiality of social conflict to occur may be reduced to a tolerable rate when constructive dialogues can be built. The dialogues should be able to facilitate the development of convergence communication and the actualization of equality principles. Higher education processes will be one the most important institutions that could bring the actualization of the principles of peacefulness into reality. This could be true when education could assure the effectiveness of value transformation processes throughout generations. The role of high education institutions to make non-violence culture to become apparent is essential. The dynamic life in a peaceful culture can only be realized when a situation of welfare, equality and well expression of communication behavior are well maintained in the community life.